Single Wideband Microstrip Patch Antenna for 5G Wireless Communication Application - Summakieh, MHD Amen; Mokayef, Mastaneh (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
A wide-band microstrip patch antenna for the next generation of wireless communication (5G) is proposed in this paper. The proposed antenna is benefited of a compact size of 30.7×22.4 mm2 at 6GHz frequency band. The proximity feed technique is used for the matching between radiating patch and the 50Ω microstrip feedline. Based on the simulation results at the chosen frequency, the proposed antenna can cover 5G requirements. The gain of 3.7dB with a directivity of 6.62 dB and a bandwidth of more than 500MHz are obtained from simulation which shows a good agreement between theory and simulation results